Chrysin and silibinin sensitize human glioblastoma cells for arsenic trioxide. (July 2017) - Gülden, Michael; Appel, Daniel; Syska, Malin; Uecker, Stephanie; Wages, Franziska; Seibert, Hasso
Abstract: Arsenic trioxide (ATO) is highly efficient in treating acute promyelocytic leukemia. Other malignancies, however, are often less sensitive. Searching for compounds sensitizing arsenic resistant tumours for ATO the plant polyphenols, chrysin and silibinin, and the ATP binding cassette (ABC) transporter inhibitor MK-571, respectively, were investigated in human glioblastoma A-172 cells. The sensitivity of A-172 cells to ATO was characterized by a median cytotoxic concentration of 6 μM ATO. Subcytotoxic concentrations of chrysin, silibinin and MK-571, respectively, remarkably increased the sensitivity of the cells to ATO by factors of 4–6. Isobolographic analysis revealed synergistic interaction of the polyphenols and MK-571, respectively, with ATO. Sensitization by chrysin was associated with depletion of cellular glutathione and increased accumulation of arsenic. In contrast, silibinin and also MK-571 increased the accumulation of arsenic more strongly but without affecting the glutathione level. The increase of arsenic accumulation could be attributed to a decreased rate of arsenic export and, additionally, in the case of silibinin and MK-571, to an increasing amount of irreversibly accumulated arsenic. Direct interaction with ABC transporters stimulating export of glutathione and inhibiting export of arsenic, respectively, are discussed as likely mechanisms of the sensitizing activity of chrysin and silibinin. Highlights: Chrysin and silibinin strongly sensitize glioblastoma cells to arsenic trioxide. Chrysin reversibly induces depletion of cellular glutathione. Chrysin and silibinin increase accumulation of arsenic and decrease the export rate. Silibinin resembles the ABC transporter inhibitor MK-571 in action.